Overview of kinematic variables for typical road vehicle maneuvers - Oza, Parth Yogesh (Univerzita Pardubice, 2022)
The aim of the work is to determine the characteristic courses of quantities during various precisely defined maneuvers of a road vehicle. The work is of an experimental nature with ERCT equipment and technology, experimental vehicles are also available. The student is expected to have a systematic approach, the ability to sort and process the measured data and then interpret them appropriately. Suitable work for those who are interested in the real behavior of the vehicle in relation to the measured data.
Přehled kinematických veličin pro typické manévry silničních vozidel
Keywords: Maneuvers; Sensors; Steering Wheel Deviation; Acceleration; Kinetic Parameters; manévry; snímače; natočení volantu; zrychlení; kinetické parametry.